Metabolic cost of level, uphill, and downhill running in highly cushioned shoes with carbon-fiber plates - Clarissa S. Whiting; Wouter Hoogkamer; Rodger Kram (Elsevier, 2022)
Background: Compared to conventional racing shoes, Nike Vaporfly 4% running shoes reduce the metabolic cost of level treadmill running by 4%. The reduction is attributed to their lightweight, highly compliant, and resilient midsole foam and a midsole-embedded curved carbon-fiber plate. We investigated whether these shoes also could reduce the metabolic cost of moderate uphill (+3°) and downhill (-3°) grades. We tested the null hypothesis that, compared to conventional racing shoes, highly cushioned shoes with carbon-fiber plates would impart the same ∼4% metabolic power (W/kg) savings during uphill and downhill running as they do during level running. Methods: After familiarization, 16 competitive male runners performed six 5-min trials (2 shoes × 3 grades) in 2 Nike marathon racing-shoe models (Streak 6 and Vaporfly 4%) on a level, uphill (+3°), and downhill (-3°) treadmill at 13 km/h (3.61 m/s). We measured submaximal oxygen uptake and carbon dioxide production during Minutes 4-5 and calculated metabolic power (W/kg) for each shoe model and grade combination. Results: Compared to the conventional shoes (Streak 6), the metabolic power in the Vaporfly 4% shoes was 3.83% (level), 2.82% (uphill), and 2.70% (downhill) less (all p < 0.001). The percent of change in metabolic power for uphill running was less compared to level running (p = 0.04; effect size (ES) = 0.561) but was not statistically different between downhill and level running (p = 0.17; ES = 0.356). Conclusion: On a running course with uphill and downhill sections, the metabolic savings and hence performance enhancement provided by Vaporfly 4% shoes would likely be slightly less overall, compared to the savings on a perfectly level race course.